PSO/SDF-1 composite hydrogel promotes osteogenic differentiation of PDLSCs and bone regeneration in periodontitis rats - Wei Zhang; Minghong Liu; Di Wu; Yuanping Hao; Beibei Cong; Lihui Wang; Yujia Wang; Meihua Gao; Yingjie Xu; Yingtao Wu (Heliyon, 2024)
Periodontitis is an inflammatory disease characterized by the destruction of periodontal tissues, and the promotion of bone tissue regeneration is the key to curing periodontitis. Psoralen is the main component of Psoralea corylifolia Linn, and has multiple biological effects, including anti-osteoporosis and osteogenesis. We constructed a novel hydrogel loaded with psoralen (PSO) and stromal cell-derived factor-1 (SDF-1) for direct endogenous cell homing. This study aimed to evaluate the synergistic effects of PSO/SDF-1 on periodontal bone regeneration in patients with periodontitis. The results of CCK8, alkaline phosphatase (ALP) activity assay, and Alizarin Red staining showed that PSO/SDF-1 combination treatment promoted cell proliferation, chemotaxis ability, and ALP activity of PDLSCs. qRT-PCR and western blotting showed that the expression levels of alkaline phosphatase (ALP), dwarf-associated transcription factor 2 (RUNX2), and osteocalcin (OCN) gene were upregulated. Rat periodontal models were established to observe the effect of local application of the composite hydrogel on bone regeneration. These results proved that the PSO/SDF-1 combination treatment significantly promoted new bone formation. The immunohistochemical (IHC) results confirmed the elevated expression of ALP, RUNX2, and OCN osteogenic genes. PSO/SDF-1 composite hydrogel can synergistically regulate the biological function and promote periodontal bone formation. Thus, this study provides a novel strategy for periodontal bone regeneration.